KONFLIK WANITA KARIR DENGAN BEBAN KERJA GANDA (DOUBLE BARDEN) - Fitriani, Hani; Susanti, Liana Dewi; Astuti, Rahma Yudi (Jurnal Studi Gender dan Anak, 2020)
The participation of women at this time rather than just demanding equal rights but also expresses its function has the meaning for the development of society Indonesia. conflict of dual role is the simultaneous occurrence of two or more role allotment, which is the fulfillment of a role that will give rise to difficulties in fulfilling the role of the other. Work-family conflict has two components, namely family affairs interfere with work, work-family conflict can arise due to the Affairs of the jobs came family. Conflicts arising as a result of household chores and all the consequences disrupt the performance of the functions of the employment of mothers in the workplace. An adaptive response, linked by characteristics and individual psychology or process which is a consecuetion of any external action, situation or event that puts the demands of special psychological and or physical person. The results of the work can be accomplished by a person or group of people in an organization in accordance with the authority and responsibility of their respective efforts in order to achieve the objectives of the Organization in question legally, does not violate the law and in accordance with morals or ethics. Double role conflict can have an impact on work stress, this shows the higher conflict dual role female employees, then the greater the also stress their work. The impact of the conflict on performance of dual role female employees indicating higher role conflict the women, then the lower the performance of them. Work stress is also impacting on the performance of female employees have, i.e. show the higher the stress of work, then the lower the pulakinerja female employees.